Trading amnesty for impunity in Timor-Leste. Issue 1 (2nd January 2016) - Jeffery, Renée
Abstract: In 1999, the United Nations made a strong stand against impunity for human rights crimes by prohibiting the inclusion of blanket amnesties in peace agreements. This article examines the impact of the UN's anti-amnesty policy on one of the first states to be affected by it, Timor-Leste. It argues that even in the absence of an amnesty, more than 15 years after independence impunity still reigns in Timor-Leste, due a lack of judicial capacity, political interference, the persistent belief that amnesties facilitate reconciliation, and an unwillingness on the part of the international community to adequately fund the justice process. That is, this article argues that the UN has oversold its position on amnesties, and that although its anti-amnesty policy is taking hold, in the case of Timor-Leste at least, justice seems as elusive as ever.